2016
DOI: 10.25273/jipm.v4i2.842
|View full text |Cite
|
Sign up to set email alerts
|

Tipe Kesalahan Mahasiswa Dalam Menyelesaikan Soal-Soal Geometri Berdasar Newman’s Error Analysis (Nea)

Abstract: <em>The students' ability to solve mathematical problems are affected directly or indirectly by their pattern of problem solving when they were attending primary and secondary schools. The result of observation shows that there are students who can not answer proving problem and take no action at all, thoughit is only at the step of understanding the problem. NEA is a frame work with simple diagnostic procedures, which include (1) decoding, (2) comprehension, (3) transformation, (4) process skills, and (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
21

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 0 publications
1
7
0
21
Order By: Relevance
“…The types of misunderstanding, transformation errors, and processing skills errors were the most common mistakes experienced by students. Errors in the understanding stage have an impact on the transformation of the problem and the improper resolution process (Utami, 2016). The error in writing the final answer did not seem dominant because only students who wrote the final answer were judged.…”
Section: Types Of Student Errors In Completing Operations Research Qumentioning
confidence: 99%
See 1 more Smart Citation
“…The types of misunderstanding, transformation errors, and processing skills errors were the most common mistakes experienced by students. Errors in the understanding stage have an impact on the transformation of the problem and the improper resolution process (Utami, 2016). The error in writing the final answer did not seem dominant because only students who wrote the final answer were judged.…”
Section: Types Of Student Errors In Completing Operations Research Qumentioning
confidence: 99%
“…Several previous studies have revealed students errors based on Newman's Error Analysis (NEA), especially statistical topics , inequality and limit functions (Erdriani & Devita, 2019), calculus for many variables (Farhan & Zulkarnain, 2019), vector analysis (Jana, 2018), analytic geometry (Junaedi, 2012), geometric shapes (Listiani, Dirgantoro, Saragih & Tamba, 2019;Mulyadi, Riyadi & Subanti, 2015), discrete mathematics (Oktaviana, 2017), plan geometry (Utami, 2016;Pamungkas & Wicaksono, 2019), differential calculus (Rahmawati, 2017), and algebra (Yusnia & Fitriyani, 2017). The results of this study indicate that generally, the most mistakes made by research subjects are errors in the transformation stage, errors in the process skills stage, errors in writing the final answer, and errors in understanding the problem.…”
Section: Introductionmentioning
confidence: 99%
“…Hal ini telah dijelaskan oleh Ayuningtyas (2013) dengan mengerjakan soal-soal HOTS maka siswa akan mencapai level-level pada kemampuan matematika siswa, dari level yang terendah sampai level yang lebih tinggi yaitu menganalisis, menciptakan, dan mengevaluasi untuk menerapkan suatu prosedur atau cara untuk menyelesaikan masalah. Selama ini penyelesaian soal matematika tipe HOTS selalu dijadikan bahan untuk melatih kemampuan pemecahan masalah siswa untuk mehadapi soal yang lebih kompleks (Ayuningtyas, 2013;Utami, 2016;Ratnaningtyas, 2016).…”
Section: Mengevaluasiunclassified
“…Kemampuan siswa dalam menyelesaikan soal-soal matematika secara langsung atau pun tidak langsung dipengaruhi oleh pola penyelesaian soal pada saat siswa duduk di bangku sekolah dasar. Hasil pengamatan peneliti menunjukkan bahwa masih terdapat siswa yang tidak bisa menjawab soal pembuktian dan tidak melakukan tindakan apapun, yang meliputi (1) decoding, (2) comprehension, (3) transformation, (4) processskill, dan (5) encoding (Utami, 2018). Di samping itu, pengembangan profesional guru saat ini mulai terbatas, tidak menjadi prioritas utama.…”
Section: Pembahasanunclassified